SROI Analysis of Social Responsibility Programs in Pagar Dewa Village - Bonifasius Santiko Parikesit; Dodo Darsono; Dien Yudithadewi; Rio Zakarias Widyandaru (Nusantara Science and Technology Proceedings, 2022)
This study aimed to analyze the impact of PT Perusahaan Gas Negara Tbk's social responsibility (CSR) program which takes place in 2019 - 2021, using the Social Return on Investment (SROI) tool. It was conducted in the company's operational area, which is located in Pagar Dewa Village, Lubai Ulu Sub District, Muara Enim District, South Sumatra Province. The research design used a mixed method, and primary data was collected through interviews with 74 relevant stakeholders from beneficiaries, government, communities, and the company. Meanwhile, the process of searching for secondary data is carried out through a literature review of digital media, books, and journals to enrich the identifying process, as well as conduct impact monetization. Particularly for impact analysis, the researcher used Sustainability Compass which initiated by Herman Daly, and further developed by Alan Atkisson. The results revealed that SROI ratio in 2019 was 1: 3.79, then increasing to 1: 6.34 in 2020 and 1: 6.35 in 2021. These points revealed that the social investment made by the company is effective and has a positive impact on society. SROI is effective for measuring social investments’ impact made by companies and helping them to carry out monitoring, improvement, and development, related to program implementation. Likewise, to be by the agenda of Sustainable Development Goals (SDGs) no. 1; without poverty, no. 3; healthy and prosperous life, no. 5; gender equality, no. 6; clean water and proper sanitation, no. 17; partnerships to achieve goals.